ORIENTASI KEWIRAUSAHAAN PETANI BROKOLI SKALA KECIL DALAM MENGHADAPI PERMINTAAN PASAR TEKSTUR (STUDI KASUS DI GAPOKTAN LEMBANG AGRI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT) - Gema Wibawa Mukti; Rani Andriani Budi Kusumo; Pandi Pardian (Paspalum: Jurnal Ilmiah Pertanian, 2017)
Broccoli is one of the prospective horticultural products to be developed, beside it has a good nutrition for health, broccoli also hasan interesting physical form. Broccoli is generally preferred by consumers of modern market, sold as fresh with adjust table size with consumer demand. On the other hand, broccoli has aperishable nature, with an unique morphological characteristics. Modern market demand requires a certainspec for broccoli, it cause farmers had tochange the way they do in their  business, so that their products are well received by the modern market. There fore, this study aims to determine the entrepreneurial orientation offarmersso it canmeet the demand ofbroccolito themodernmarket. Broccoli’s Farmer has a high entrepreneurial spirit, as seen from the orientation of farmers in view the future. Farmers see the modern market as an alternative market with a huge potential market in the future, so that the farmers do a variety of creative effort to make their business performance more efficiently so it can serve the  modern market better. The method usedinthisstudyis thecase studies method, theanalysis techniqueused isdescriptive qualitativeanalysis. Research shows that broccoli farmers as an entrepreneur has an unique characteristics and valuesin running their business. Broccoli farmes entrepreneurial orientation in Kecamatan Lembang emphasizes the creation of business innovation, always doing to do the improvement process of their supply chain product, namely with implementing strategies for business collaboration with other actors in the broccoli supply chain. They also always proactivein receivinga request from the modern market as an alternative market for their business, so their businesses can be more competitive and be able to runcontinuously.